PENGGUNAAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA SUBTEMA KEBERSAMAAN DALAM KEBERAGAMAN - Anjani, Dian; Roni Hamdani, Acep (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2018)
Research this background by activities learn who is still centered to the teacher inside form method lecture so that student less active and results learn student still on under KKM. Research this aim for fix it and increase results learn student on subtheme togetherness in diversity through discovery learning models . Research this use method research action class at SDN Cikitu 03 grade IV with number of 30 students . Research action class this consists of of 3 cycles , each cycle there is two meeting with covering activities planning , implementation , observation or observation and reflection . Based on observation and reflection conducted on research this obtained results planning learning on the first cycle of 70%. On cycle II planning learning increase to be 75%, at cycle III obtains 86% yield . Implementation learning on cycle I got 72%. On cycle II obtains results 80%. On cycle III becomes by 90%. H acyl an ti penili Act teacher's behavior with apply syntax discovery learning on cycle I obtained 66% result with category enough good. On cycle II obtains 76% with criteria good. On cycle III obtains results 86 % with criteria very good. Response student to teacher's behavior on cycle I obtained percentage of 64 , 33 % or categorized as enough good. Cycle II obtains 74 , 33 % or categorized as response student good. On cycle III obtains 86.61 % or said response student very good. Results learn on the cycle I reaches KKM value by 37% to criteria enough , cycle II reaches KKM as much as 57% with criteria well , cycle III reaches KKM value as much as 90% with criteria very good. this showing that use of discovery learning models could increase results learn student on subtheme togetherness in diversity in class IV SDN Cikitu 03. With Thus , the use of discovery learning models could made wrong one learning model for applied on theme beautiful togetherness subtheme togetherness in diversity .